2021
DOI: 10.3389/fcell.2021.748831
|View full text |Cite
|
Sign up to set email alerts
|

IL-18-Mediated SLC7A5 Overexpression Enhances Osteogenic Differentiation of Human Bone Marrow Mesenchymal Stem Cells via the c-MYC Pathway

Abstract: Objective: To investigate the role of IL-18 in the regulation of osteogenic differentiation in human bone marrow mesenchymal stem cells (hBMSCs).Methods: To assess whether IL-18 affects the osteogenic differentiation of hBMSCs through the c-MYC/SLC7A5 axis, IL-18 dose-response and time-course experiments were performed to evaluate its impact on osteogenic differentiation. To confirm osteogenic differentiation, alizarin red staining calcium measurement were performed. RT-qPCR and western blotting were used to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…We further observed downregulation of many other amino acid transporters such as Slc1a5 and Slc7a5 by long-term hyperglycemia. The lack of these two glutamine transporters has been associated with impaired differentiation of osteoblasts ( Ni et al, 2021 ; Sharma et al, 2021 ; Shen et al, 2021 ) indicating that the glutamine/glutamate to proline ratio may be important for osteoblast differentiation and proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…We further observed downregulation of many other amino acid transporters such as Slc1a5 and Slc7a5 by long-term hyperglycemia. The lack of these two glutamine transporters has been associated with impaired differentiation of osteoblasts ( Ni et al, 2021 ; Sharma et al, 2021 ; Shen et al, 2021 ) indicating that the glutamine/glutamate to proline ratio may be important for osteoblast differentiation and proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…SLC7A5 and c-MYC play important roles in the IL-18-induced expression of osteogenic markers in hBMSCs. IL-18 upregulates the expression of SLC7A5 and c-MYC at the early stage of hBMSC osteogenic differentiation, and SLC7A5 and c-MYC inhibition blocks the osteogenic differentiation induced by IL-18 ( 34 ). The bone density of elderly patients with osteoporosis increases significantly after anti-osteoporosis treatment.…”
Section: Discussionmentioning
confidence: 99%
“…[ 59 ] Ni F. et al found that via the SLC7A5/c-MYC pathway IL-18 promoted the osteogenic differentiation of hBMSCs, which showed that MYC was also an important factor in osteogenic differentiation. [ 60 ] TNF-α can regulate the early development of ONFH by mediating osteoblast autophagy and apoptosis [ 61 ] and the onset of steroid-induced osteonecrosis of femoral head is influenced by TNF-α and hypoxia history, [ 62 ] so TNF is an important target of ONFH. IL6 is an important cytokine and ONFH is accompanied by significant inflammatory response, so IL6 is an important target in the process of ONFH.…”
Section: Discussionmentioning
confidence: 99%